Вып. 7, 2002; Ежегодник ТПУ (2002, 2002)
В книге представлены статистические и справочные данные по результатам работы Томского политехнического университета в 2001 году. Структура ежегодника отражает основные направления деятельности университета, значительная часть издания посвящена информации о факультетах и научно-исследовательских институтах. Предназначена для широкого круга отечественных и иностранных читателей, интересующихся системой высшего образования России. Extensive statistic and directorial data on the results of the TPU activities in 2001 are represented in this book.Major trends of the university activities are reflected in the Year-Book, the significant part of which is devoted to information about faculties and research institutes of TPU.The book is intended for a wide use of domestic and foreign readers interested in the Russian system of higher education.